2021
DOI: 10.3390/brainsci11050574
|View full text |Cite
|
Sign up to set email alerts
|

The Lost Neural Hierarchy of the Autistic Self—Locked-Out of the Mental Self and Its Default-Mode Network

Abstract: Autism spectrum disorder (ASD) is characterized by a fundamental change in self-awareness including seemingly paradoxical features like increased ego-centeredness and weakened self-referentiality. What is the neural basis of this so-called “self-paradox”? Conducting a meta-analytic review of fMRI rest and task studies, we show that ASD exhibits consistent hypofunction in anterior and posterior midline regions of the default-mode network (DMN) in both rest and task with decreased self–non-self differentiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 136 publications
(221 reference statements)
1
6
0
Order By: Relevance
“…This resembles the findings in anxiety disorders which symptomatically may be mirrored in an unstable social self as psychological trait feature in both ASD and SAD. However, unlike in SAD, subjects with ASD exhibit decreased task-related activity in response to self-referential and emotional stimuli which symptomatically may be reflected in a decreased mental self (Lian and Northoff 2021; as distinguished from the increased mental self with higher self-attention in SAD). Accordingly, our combined rest-task approach holds the promise of providing differential-diagnosis of different changes of self in a variety of different psychiatric disorders like ASD (Lian and Northoff 2021) and schizophrenia (Northoff and Gomez-Pillar 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resembles the findings in anxiety disorders which symptomatically may be mirrored in an unstable social self as psychological trait feature in both ASD and SAD. However, unlike in SAD, subjects with ASD exhibit decreased task-related activity in response to self-referential and emotional stimuli which symptomatically may be reflected in a decreased mental self (Lian and Northoff 2021; as distinguished from the increased mental self with higher self-attention in SAD). Accordingly, our combined rest-task approach holds the promise of providing differential-diagnosis of different changes of self in a variety of different psychiatric disorders like ASD (Lian and Northoff 2021) and schizophrenia (Northoff and Gomez-Pillar 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Going beyond anxiety disorder, the neuronal and psychological changes in self may also serve for differential diagnosis of anxiety disorders in general and others. For instance, a recent study observed hypoactivity in resting state in autism spectrum disorder (ASD; Lian and Northoff 2021). This resembles the findings in anxiety disorders which symptomatically may be mirrored in an unstable social self as psychological trait feature in both ASD and SAD.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of brain dynamics, long-range correlations, auto-correlation window decay, and scaling behavior have been utilized to characterize intrinsic neuronal time scales embedded in EEG/MEG/fMRI source signals, and to associate changes of dynamical characteristics with brain regions' functions, physiological states, and conditions 32,34,35,87,88 . In parallel to this important line of research within the reductionist framework, investigations have focused on integrative coupling, coherence, and synchronization phenomena in brain dynamics and network-based approaches to understand emerging behaviors through structural and functional connectivity 5,13,32,37,[39][40][41][42][43][44][45][47][48][49][50][51][52][53][55][56][57]66,[89][90][91][92][93][94][95][96][97] . Our study focuses on coupling forms and network interactions among dominant and non-dominant brain rhythms that are simultaneously present at a given cortical location during a given physiological state.…”
Section: Discussionmentioning
confidence: 99%
“…Other works have examined coupling and coherence of a given cortical rhythm across brain locations, extending this connectivity approach to different cortical rhythms separately 5,[36][37][38] . Structural and functional connectivity studies have predominantly utilized fMRI data or cross-correlation on integrated EEG signals from different cortical locations [39][40][41][42][43][44][45][46] . In recent years, research groups have explored the interaction between cortical rhythms for selected pairs (e.g., γ-α, γ-β, γ-θ, β-θ) specifically in the context of working memory, perception, cognitive function, and consciousness [47][48][49][50][51][52][53][54][55][56][57] .…”
mentioning
confidence: 99%
“…The central area that generates the subjective awareness of “self” as a reference to the surrounding environment is the cortical mediomedial structure within the DMN, which is active during self-resuming mind wandering ( 148 ). Activity in the DMN (medial prefrontal cortex, anterior/medial cingulate, and inferior parietal lobule), while performing self-referential tasks was consistently lower in the ASC in various experimental paradigms, suggesting that the highest-order self-concept is difficult to form ( 150 ).…”
Section: Mismatch Between Top-down Expectation and Bottom-up Percepti...mentioning
confidence: 99%